2021
DOI: 10.1055/s-0041-1735385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Otoacoustic Emissions

Abstract: Introduction Caffeine is consumed everyday in a variety of ways by a large population around the world, including coffee, tea, and soft drinks. Therefore, there is a significant need to explore the effects of caffeine on human auditory system. The present study aimed to investigate the effect of caffeine on cochlea using distortion product otoacoustic emission (DPOAE). Materials and Methods Thirty-three young adults were recruited for the study. The effect of caffeine on cochlea was assessed using DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Results of the present study showed no significant effect of coffee on the amplitude of TEOAE. This finding is consistent with those of Drepath et al 23 which showed no effect of coffee on the amplitude of DPOAEs in humans. These findings suggests no effect of caffeine on the amplitude of OAEs in humans.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Results of the present study showed no significant effect of coffee on the amplitude of TEOAE. This finding is consistent with those of Drepath et al 23 which showed no effect of coffee on the amplitude of DPOAEs in humans. These findings suggests no effect of caffeine on the amplitude of OAEs in humans.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, Bobbin 27 reported an effect of caffeine on the amplitude of DPOAE in animal study. Therefore, although Drepath et al 23 reported no effect of coffee on the amplitude of OAE in humans; similar investigations should be conducted before generalizing the results. Thus, the first objective of the present study was to investigate the effect of coffee on the amplitude of TEOAE.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies have been carried out to investigate the effect of caffeine on auditory evoked potentials, 11 20 speech perception, 21 , 22 and OAEs. 23 Few studies have investigated the effect of caffeine on the auditory brainstem response (ABR). Findings from these investigations have showed significantly shorter latency and larger amplitude for ABR peaks following caffeine ingestion.…”
Section: Introductionmentioning
confidence: 99%